If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y + 7 = 23 Reorder the terms: 7 + 8y = 23 Solving 7 + 8y = 23 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 8y = 23 + -7 Combine like terms: 7 + -7 = 0 0 + 8y = 23 + -7 8y = 23 + -7 Combine like terms: 23 + -7 = 16 8y = 16 Divide each side by '8'. y = 2 Simplifying y = 2
| 8(3x-2)+6=7(-5x-20)-1 | | x^2+12x=-43 | | 3p-2-7p=-5+p-4p | | 3x^2*8x^5= | | n-3=-4n-(n-3) | | 2y-3y+-1=4 | | -7(3r-4)=-20+9r | | 28-13.8x=-54.8 | | 4s-12*(s-2)=s | | 20z+3z-21z-1=13 | | -78=6U+12 | | 3x-3+x-3=90 | | (6x^3y^2)(-2x^2y)= | | -6+3(1-8k)=27 | | -22=2-3r+7r | | 5(3x-6)=10 | | -0.5s=-28 | | 198=g+12 | | 42=-2(v-8) | | 7+0=x | | -21=9d-7d | | 220=g+70 | | 5(c-6)c+11=24 | | -12=6(x+7) | | 7+y+12y=7 | | -8n+2=-3n-3 | | -5p-24=21(-1+3p) | | b+3-9=29 | | 4(-3+v)=36 | | f(5)=4x-3 | | -5(2s+2m)= | | -111=-3(1+6n) |